2023
DOI: 10.3390/agriculture13050967
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Determinants of Turkish Farmers’ Health and Safety Behaviors: An Application of the Extended Theory of Planned Behavior

Abstract: Background: Structural and behavioral factors are among the causes of occupational accidents in agriculture. The SACURIMA Cost network developed a questionnaire to measure the determinants of farmers’ safety behavior based on the extended theory of planned behavior (TPB). Extended TPB adds subjective norms, subjective control, physical barriers and safety culture to TPB. Objective: The aim of this study is to test the psychometric properties of the “Farmers Safety Behaviors questionnaire” developed by the SACU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The mean age of the household heads was 44 years, and significantly different between households that were willing and those which were not willing to pay for private extension services. The mean age of the farmers in Gibi District attests to the fact that they were still energetic and active in their farming business, which contrasts with studies in other SSA countries where farmers have been reported to be older [43,49]. According to [63], only farmers below the age of 50 possess the strength to carry out farming works.…”
Section: Farmers' Socio-demographic Profilesmentioning
confidence: 73%
See 2 more Smart Citations
“…The mean age of the household heads was 44 years, and significantly different between households that were willing and those which were not willing to pay for private extension services. The mean age of the farmers in Gibi District attests to the fact that they were still energetic and active in their farming business, which contrasts with studies in other SSA countries where farmers have been reported to be older [43,49]. According to [63], only farmers below the age of 50 possess the strength to carry out farming works.…”
Section: Farmers' Socio-demographic Profilesmentioning
confidence: 73%
“…Therefore, behavioral intention precedes attitude towards the behavior, which the individual evaluates as favorable or unfavorable. The TPB has been variously applied to examine the sustainable extension of food preparation techniques in rural areas of Taiwan [41] to predict WTP for municipal solid waste management in Beijing [42], and to assess the health safety behavior of farmers in Turkey [43].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation